Peningkatan Pemahaman Peserta Didik Kelas VII Melalui Metode Inside Outside Circle dengan Bantuan Media Video Animasi - Aziz Kurniawan (Jurnal Pendidikan, 2020)
The research conducted has a purpose is to provide improvement to students through the Inside Outside Circle method with the help of media video animation. The inside outside circle method trains students to increase their understanding of learning because the learners ' learning process exchanges information between each other. The results of this study showed that the learning that applied inside outside Circe with the help of animated video gave the contribution for students to improve understanding in learning. It is noted that before the average learning process pretests in the experimental class was 38.055. The control class is 42.167. After the treatment, there was an increase that the average posttest of the experimental class was 63.43. The control class is 53.46. The result of the increase was measured through test-t which was then concluded that the value of Thitung > this with a value of 4.24 > 1.99 that explains the understanding of learners using the Inside Outside Circle model of video animation media help better than conventional learning